Correction of Alar Retraction Based on Frontal Classification - Kim, Jae Hoon; Song, Jin Woo; Park, Sung Wan; Bartlett, Erica; Nguyen, Anh H. (Seminars in Plastic Surgery, 2015)
Among the various types of alar deformations in Asians, alar retraction not only has the highest occurrence rate, but is also very complicated to treat because the ala is supported only by cartilage and its soft tissue envelope cannot be easily stretched. As patients' knowledge of aesthetic procedures is becoming more extensive due to increased information dissemination through various media, doctors must give more accurate, logical explanations of the procedures to be performed and their anticipated results, with an emphasis on relevant anatomical features, accurate diagnoses, detailed classifications, and various appropriate methods of surgery.
Keywords: alar retraction; alar spreader graft; cartilage graft; nasal hinge